The association between soy consumption and metabolic syndrome in Chinese adults: a cross-sectional study - Hidayat, Khemayanto; Huang, Yan-Hui; Qian, Xiao-Yan; Chen, Xiao-Fang; Yu, Lu-Gang; Zhou, Hui; Qin, Li-Qiang (Frontiers in Nutrition, 2025)
BackgroundEvidence on the association between soy consumption and metabolic syndrome (MetS) remains limited and inconclusive. This study aimed to investigate the relationship between soy intake and the prevalence of MetS and its components in a Chinese population.MethodsA cross-sectional analysis was conducted among 5,107 adults residing in Suzhou Industrial Park, Suzhou, China. Dietary intake was assessed using an interviewer-administered food frequency questionnaire. MetS was defined according to the Joint Interim Statement (JIS) criteria. Logistic regression models were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for MetS and its components in relation to soy consumption, adjusting for potential confounders.ResultsEach 25 g/day increase in soy consumption was associated with lower odds of MetS (OR 0.95, 95% CI 0.92–0.98), elevated waist circumference (OR 0.97, 95% CI 0.94–0.99), elevated triglycerides (OR 0.94, 95% CI 0.91–0.96), reduced HDL-cholesterol (OR 0.95, 95% CI 0.92–0.97), and elevated blood pressure (OR 0.97, 95% CI 0.94–0.99), but not elevated fasting blood glucose. These associations were more pronounced and consistent among women. Menopausal status did not significantly modify the associations.ConclusionHigher soy consumption was associated with a lower prevalence of MetS and most of its components, particularly among women. These findings highlight the potential role of soy foods in metabolic health and warrant prospective studies to clarify causal relationships, assess individual soy food types, and explore sex- and menopause-specific effects.